Disability in Patients Presenting With Spinal Tuberculosis - Obaid, Ramsha Nasir; Muhammad, Muhammad Imran Jan; Kumar, Ramesh; Ali, Farhad; Khulsai, Muhammad Sameer; Hussain, Syed Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Spinal tuberculosis (TB) is the most common form of skeletal TB and a major contributor to neurological morbidity in endemic regions. While clinical severity and radiological extent are often used to estimate outcomes, functional disability remains a complex and underexplored consequence of spinal TB, especially in resource-constrained settings. Understanding the incidence and correlates of disability is critical for guiding prognostication and management strategies. Objective: To assess the incidence of disability in patients presenting with spinal tuberculosis. Methods: In this prospective, cross‐sectional study, we enrolled consecutive patients presenting to the Department of Neurosurgery outpatient clinic at CHK over a six‐month period November 2024 till April 2025. Eligible participants were adults aged 18–55 years with radiological evidence of spinal tuberculosis on MRI. Patients were excluded if they had a prior history of cerebrovascular accident, any previous spinal, thoracic, or lower limb surgery, congenital musculoskeletal anomalies (e.g., cerebral palsy, limb amelia), poliomyelitis, or any other neurological disorder unrelated to spinal tuberculosis Results: Among the 13 patients with lumbar lesions, 4 were disabled versus 15 non‐disabled; thoracic involvement saw 4 disabled and 9 non‐disabled, and cervical disease 5 versus 8 (p = 0.593). Disability similarly did not correlate with the number of vertebrae involved (p = 0.369): 4 of 15 single-level cases were disabled versus 11 non-disabled; 4/10 two-level; 1/9 three-level; and 5/11 four-level. Motor deficit severity also showed no significant effect (p = 0.330): 5 of 12 mild, 3 of 11 moderate, 5 of 12 severe, and only 1 of 10 with no motor deficit were classified as disabled. Finally, sensory deficits were present in 8 disabled versus 14 non-disabled patients with no significant difference (p = 0.337). Overall, although nearly half the cohort exhibited some functional impairment, lesion location, extent of vertebral involvement, and neurological deficit at presentation did not predict disability in this sample. Conclusion: Early presentation and prompt management in our cohort resulted in minimal disability, suggesting that timely intervention may outweigh anatomical disease burden in predicting functional outcomes.